2010
DOI: 10.1371/journal.pone.0013852
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Age on Inflammatory and Coagulation-Fibrinolysis Response in Patients Hospitalized for Pneumonia

Abstract: ObjectiveTo determine whether inflammatory and hemostasis response in patients hospitalized for pneumonia varies by age and whether these differences explain higher mortality in the elderly.MethodsIn an observational cohort of subjects with community-acquired pneumonia (CAP) recruited from emergency departments (ED) in 28 hospitals, we divided subjects into 5 age groups (<50, 51–64, 65–74, 75–84, and ≥85). We measured circulating levels of inflammatory (TNF, IL-6, and IL-10), hemostasis (D-dimer, Factor IX, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
37
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 54 publications
(61 reference statements)
8
37
2
2
Order By: Relevance
“…Our results suggest that an episode of infection accelerates dementia. A potential mechanism to explain this association could be persistent inflammation in the systemic circulation or in the brain or due to activation of other aspects of the innate immune response, as evidenced in observational human studies (49, 1315) and in animal models (1012, 45). For example, a single lipopolysaccharide injection in animals causes chronic neuroinflammation, long-term cognitive deficits, and accelerates neurodegenerative conditions (1012).…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that an episode of infection accelerates dementia. A potential mechanism to explain this association could be persistent inflammation in the systemic circulation or in the brain or due to activation of other aspects of the innate immune response, as evidenced in observational human studies (49, 1315) and in animal models (1012, 45). For example, a single lipopolysaccharide injection in animals causes chronic neuroinflammation, long-term cognitive deficits, and accelerates neurodegenerative conditions (1012).…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies longitudinally report age-related differences in inflammatory biomarkers, as most studies have been cross-sectional at variable times during their hospital course. Existing data are contradictory on whether older adults have greater or suppressed acute inflammation and whether this contributes to the poorer outcomes of severe sepsis in older adults (7, 8, 15, 16). In this study, we analyzed six novel biomarkers of inflammation measured serially for 72 hours as part of a large, multicenter longitudinal cohort of emergency department (ED) patients admitted for sepsis (14).…”
Section: Introductionmentioning
confidence: 99%
“…MILBRANDT et al [47] identified that significant pro-thrombotic effects and elevation of coagulation markers persisted throughout hospital stay and occurred even in patients with clinically very mild pneumonia. Data from the same group also suggest that elevation of coagulation markers is greatest in elderly patients with pneumonia, the group at greatest cardiovascular risk [48].…”
Section: Platelet Activation and Thrombosismentioning
confidence: 93%